Under the dam [and other stories] - Constantine, David 1944- (Comma Press, 2005)
Contents: The loss - The necessary strenght - In another country - All on video - Estuary - The red balloon - A Paris story - Life after death - Mouse and bear - Self-portrait - Visiting - The afterlife - Sleepless - Under the dam.